Synthesis and characterization of alginate-hydroxyethyl cellulose microspheres as drug delivery system for naproxen sodium - Pescos, Charisse Joy H.
Naproxen sodium is a non-steroidal anti-inflammatory drug (NSAID) used for treatment of pain, inflammation and conditions such as arthritis. The use of NSAIDs has been observed to cause adverse effects in the gastrointestinal tract (GIT). To decrease side effects in GIT, sodium alginate (SA) and hydroxyethyl cellulose (HEC) were used to synthesis pH-sensitive biocompatible and biodegradable polymer microspheres. The microspheres were prepared by extruding a mixture of polymer and drug solution via needle into 4 wt. percent calcium chloride solution. Different formulations were developed by varying the concentrations of HEC, calcium ion, polymer and NS. The resulting microspheres have increasing sizes, (1.062 mm to 1.266m), as SA/HEC ratio increases as shown by the morphological analysis using scanning electron microscope. Entrapment efficiencies increase at increasing SA content (51.36 percent and 82.65 percent). The microspheres were further tested for swelling ratios and dissolution rates using simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) as media. Swelling test reveal pH sensitivity of the alginate-hydroxyethyl cellulose microspheres with higher swelling observed in slightly basic SIF (up to 6000 percent) compared with acidic SGF (up to 300 percent). Dissolution rates show the non-release of drugs in acidic SGF but effectively releases drug in slightly basic SIF. These release profiles were mathematically modelled to study the release kinetics of naproxen in the polymer matrix blend. Increasing diffusivities result from increasing HEC and NS content.